UNDANG-UNDANG DEPOSIT DI INDONESIA DAN MALAYSIA: PERBANDINGAN DAN PENERAPANNYA - Afdini Rihlatul Mahmudah; Zulfikar Zen; Utami Budhi Rahayu Hariyadi (Ikatan Pustakawan Indonesia, 2017)
This purpose of this research is to describe the implementation of the Law on Deposit at the National Library of Indonesia and the National Library of Malaysia. The method used was a case study. The data was collected through interview, study documents, and observation. The results show that the implementation of the Law on Deposit in Indonesia has occurred since 1990, while in Malaysia since 1986. In general, the Deposit Law between the two countries is almost the same, but there are some differences among others: a) Total collections submitted to the National Library, in Indonesia two (2) copies of the print publication and 1 (one) copy of non-print publications have to be submitted, while in Malaysia five (5) copies of print publications and two (2) copies of non-print publications. b) Storage, the collections in Indonesia are stored at the National Library in Jakarta, while Malaysia have four storages, namely at the National Library of Malaysia, in the Region Sungai Besi Kuala Lumpur, Sabah and Penang. c) Rewards price, in Indonesia the collections are handed over for free while in Malaysia the price of books that are considered expensive receive a reimbursement of 30% of the issue price. d). The sanctions, violations of the implementation of the Law on Deposit in Indonesia will be 5 million rupiah fine or 6 months imprisonment, while in Malaysia the fine is only 3.000 ringgit. The two countries have not been up to implement Deposit Law and still focused on commercial publications.